PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI METODE PARTICIPATORY LEARNING PADA MATERI KELILING DAN LUAS BANGUN DATAR - Fredy Kustanto (JURNAL MITRA SWARA GANESHA, 2015)
ABSTRACT Participation of students in the following study is still relatively lacking. It is a reality in schools showed that the learning process that takes place in the class III SD N IV Ngadirojo actually engage students, for example, when teachers explain students listen and then record the lessons given. However, most students rarely involved in asking questions or expressing their opinions. Through action research is expected to increase in the enthusiasm of students in mathematics in elementary N IV Ngadirojo. Master class as research partners strongly support the efforts to achieve these conditions. Implementation of Participatory Learning makes students more interested and excited in participating in the learning of mathematics because students are not just sitting listening to the explanation of the teacher, but also actively involved when learning takes place. Of the implementation of the PTK that have been done show an increase learning outcomes in cycles 3, amounting to 87% of students completed the study.